Physical and mechanical properties of maize extrudates as affected by the addition of chia and quinoa seeds and antioxidants - Cueto, Mario Alberto; Porras-Saavedra, Josefina; Farroni, Abel Eduardo; Alamilla-Beltrán, Liliana; Schöenlechner, Regine; Schleining, Gerhard; Buera, María del Pilar (2018)
The physical and mechanical properties of maize extrudates have been analyzed in relation to the addition of quinoa flour and two novel ingredients, chia and powder extract of purple corn with antioxidant properties. Maize flour and mixtures with 20% quinoa or 5% chia or 2% antioxidant powder were extruded with a double screw extruder. Physical properties like expansion rate, density, humidity, and mechanical and acoustic properties using a cutting test were measured. Mixtures with chia showed a lower expansion rate, probably related to the higher lipid content of the final mixture. On the other side, quinoa favored the expansion rate compared to maize flour. This was in correlation with the density results, being the quinoa extrudates the ones with the smallest density values. Extrudates with quinoa resulted in a smoother structure while chia addition tended to generate a rougher surface. Also, the addition of antioxidant powder decreased the surface roughness.